Biodiversity Reporting Among Malaysian Companies: does the Risk Level Matter? - Husin, Norhayati Mat; Remali, Azrinawati Mohd; Alrazi, Bakhtiar (International Journal of Engineering and Technology, 2018)
As Malaysia launched its National Key Economic Areas, biodiversity has been identified as one of the entry point projects for one of the sectors that will drive Malaysia towards high-income status i.e. tourism. Biodiversity, however, is facing a crisis, due to the development of business operation that has direct or indirect contribution to biodiversity loss. Despite the growing concern on biodiversity issue, previous studies have put more focus on general sustainability or environmental reporting issues. This paper aims to provide an analysis on the extent of biodiversity information disclosed by the top 100 Malaysian public listed companies and to see whether there is significant difference, in terms of reporting, between companies from different categories of biodiversity risk. The findings show 80 of the Malaysian companies disclose information regarding biodiversity with ‘mission statement’ being the highest reported biodiversity related item. There is also significant difference, in the context of biodiversity reporting, between companies from different categories of biodiversity risk. Further analysis shows companies with higher biodiversity risk (red-zone) provide more reports on biodiversity related information leading to a statistically significant difference from companies with lower biodiversity risk i.e. amber-zone and green-zone.